Les orchidéesdelarégiondeSouk-Ahras(Nord-est algérien) :inventaire,écologie,répartitionetenjeuxde conservation - Boukehili, K; Boutabia, L; Telailia, S; Menaa, M; Tlidjane, A; fMaazi, M.C; Chefrour,A; Saheb, M; Véla,E. (My University, 2022)
SUMMARY.— Orchids of Souk-Ahras province (Northeast of Algeria) : inventory, ecology, distribution and conservation concerns.— Algerian orchids became better known during the last years, but certain regions, such as the province of Souk-Ahras (Northeast of Algeria), remain under-prospected. This study is a phytoecological approach, which aims to improve the knowledge of the orchids of this province. A series of targeted surveys has been realized between 2011 and 2015 when we were able to check 7 genera, including 27 species/subspecies and 1 hybrid. Some species are widely distributed throughout the province territory, while others are very localized. Only 18 municipalities among the 26 in the province are concerned by this distribution and are represented by 73 stations including at least one species of orchids. Among the observed taxa 7 are qualified as rare or very rare at national level, at least 3 are Algerian-Tunisian endemics (Ophrys battandieri, Ophrys numida, Orchis pauciflora subsp. laeta) and at least 3 are threatened at global scale (Ophrys atlantica, VU ; Orchis patens subsp. patens, EN ; Serapias lingua subsp. stenopetala, CR). The orchids of Souk-Ahras province often grow on limestone, clayey or siliceous soils, in a subhumid bioclimate rarely semi-arid, at all altitudes of the province, from 500 to 1400 m. This variety of species highlights the taxonomic richness and confirms the interest of prospecting this region that was neglected by orchidologists